Enhancing routing efficiency in highway environments of vehicular ad hoc networks through fuzzy logic-based protocols - Al Shugran, Mahmoud A.; Abu-Al-Aish, Ahmad; Jaradat, Ghaith M.; Alghamdi, Fahad Ali; Alqurni, Jehad Saad; Alsmadi, Mutasem Khalil; AL Hawamdeh, Majd; Alfagham, Hayat; Badawi, Usama A.; Gharaibeh, Mutaz Falah (Institute of Advanced Engineering and Science, 2025)
The predictive directional greedy routing (PDGR) protocol is widely utilized in highway settings within vehicular ad hoc networks (VANETs). However, PDGR encounters a notable challenge when packets lack a suitable vehicle directionally, leading to network disconnections. This triggers a shift to carry and forward recovery mode due to outdated neighbor information in the vehicle's neighbor table (VNT). To address this, our study proposes an improved fuzzy logic-based improved PDGR (IPDGR). This novel algorithm dynamically adjusts beaconing intervals based on real-time network dynamics. Through comprehensive evaluation using VANET simulators, IPDGR demonstrates superior performance compared to PDGR and directional greedy routing (DGR) protocols across various metrics including Inconsistency of vehicle's neighbor's table (IVNT), packet delivery ratio (PDR), routing path length (RPL), and number of hole problem occurrence (NHPO).